Pembaharuan dalam Mashaf Rasm 'Uthmani: Suatu Sorotan Sejarah - Hj Abd Ghani, Abd Rahman; Abdullah, Mustafa (Jurnal Usuluddin, 2002)
The recitation of the Qur'an by Muslims is guided by illustrated signs, symbols and dots. These illustrations has been created or introduced by post-companion scholars. They were introduced in order to guide the 'Ummah how to recite the Qur'an correctly. In doing so, there are different views pertaining to various types of symbols, signs and dots to be used. In conclusion, Muslim are allowed to choose whatever signs available to them to use in writing the holy Qur'an.